The relationship between food security, dietary patterns, and socioeconomic status in Iranian pregnant women - Barzegar, Ali; Abbaszadeh, Nasrin; Sarbakhsh, Parvin; Jafari, Azam (Progress in Nutrition, 2019)
Background and aim: According the World Health Organization definition,food security is defined as physical, social and economic access to nutritionally adequate and safe food for a healthy and active life. Inappropriate diet in pregnancy may have detrimental effect on fetus. The aim of this study was to investigate the association of socio-economic variables with dietary patterns in food secure and not secure pregnant women of Khodabandeh, Zanjan, Iran. Materials and methods: Two hundred eight pregnant women were enrolled to the current study. The housholds food security was assessed using 18 item USDA questionnaire. Dietary patterns were identified by principal components analysis using a validated 132 item food frequency questionnaire (FFQ). Results: This population-based cross-sectional study was carried out on 208 pregnant women with mean age of 28.08± 5.99. The prevalence of food insecurity was 33.6%. Monthly income, family number, dietary supplements, parents educationlevel have role in food insecurity status.Three dietary patterns were identified: Traditional, western and Un-healthy snack. Conclusion: Considering the asociation of socio-economic factors with food security status in pregnant women and determining dietary patterns during pregnancy, these factors should be considered to provide effective screening during the pregnancy and reduce the risk of food insecurity.